Overexpression of AtruLEA1 from Acer truncatum Bunge Enhanced Arabidopsis Drought and Salt Tolerance by Improving ROS-Scavenging Capability - Shaofeng Li; Huijing Meng; Yanfei Yang; Jinna Zhao; Yongxiu Xia; Shaoli Wang; Fei Wang; Guangshun Zheng; Jianbo Li (Plants)
Late embryonic developmental abundant (LEA) genes play a crucial role in the response to abiotic stress and are important target genes for research on plant stress tolerance mechanisms. Acer truncatum Bunge is a promising candidate tree species for investigating the tolerance mechanism of woody plants against abiotic stress. In our previous study, AtruLEA1 was identified as being associated with seed drought tolerance. In this study, LEA1 was cloned from A. truncatum Bunge and functionally characterized. AtruLEA1 encodes an LEA protein and is located in the nucleus. Phylogenetic tree analysis revealed a recent affinity of the AtruLEA1 protein to AT3G15760.1. Overexpression of AtruLEA1 resulted in enhanced tolerance of Arabidopsis thaliana to drought and salt stress and heightened the ABA sensitivity. Compared to wild-type (WT) plants, plants with overexpressed AtruLEA1 exhibited increased activities of antioxidant enzymes under drought stress. Meanwhile, the ROS level of transgenic Arabidopsis was significantly less than that of the WT. Additionally, the stoma density and stoma openness of AtruLEA1 Arabidopsis were higher compared to those in the WT Arabidopsis under salt and drought stress conditions, which ensures that the biomass and relative water content of transgenic Arabidopsis are significantly better than those of the WT. These results indicated that AtruLEA1 was involved in salt and drought stress tolerances by maintaining ROS homeostasis, and its expression was positively regulated by abiotic stress. These results indicate a positive role of AtruLEA1 in drought and salt stress and provide theoretical evidence in the direction of cultivating resistant plants.